CADD-50. AN OLD STORY (MGMT) IN AN EXPANDED CONTEXT (NATIONAL CANCER DATABASE). (5th November 2018) - Konduri, Santhi; Singh, Maharaj; Rovin, Richard; Bobustuc, George; Kassam, Amin
Abstract: BACKGROUND: O 6 -methylguanine-DNA methyltransferase (MGMT), a DNA repair protein, which is expressed in majority of cancers including glioblastoma multiforme (GBM), a predictive biomarker in the alkylator based treatment of gliomas. OBJECTIVE: The objective of this study is to confirm the MGMT's role as a predictive biomarker and to re-evaluate the potential MGMT, patient subset specific, prognostic role using the National Cancer Database (NCDB). METHOD: We used the NCDB to identify GBM patients with MGMT (N=5934) registered from 2010 through 2014 in which MGMT status was detected. Hyper methylation was detected in 40.65% patients while the remaining 59.35% were unmethylated (low methylation scores). The mean, and SD age of the patients was 60.8 ± 12.7 years. The patient population included 90.6% white, 4.95% black, 4.42% of other races (Hispanic and Asians), out of these, males 57.7% and females 43.3 %. RESULTS: The incidence of GBM was 11.5% in 2010 and 34.29% in 2014. Overall survival (OS) among GBM patients was higher among methylated patients regardless of therapeutic intervention (p <0.001). Unadjusted mortality risk was higher in unmethylated patients (HR=1.22; 1.09–1.34). However adjusted for other demographic and therapeutic factors the hazard ratio was further increased to 1.5 (95% CI; 1.43–1.61). The other predictors of mortality were male (HR=1.10; 1.04–1.17), white (HR=1.31; 1.12–1.52), and black vs others (HR=1.22; 1.00–1.52), 5-year increase in age (HR=1.17; 1.15–1.19), no surgical resection (HR=2.00; 1.81–2.20) and no radiation treatment (HR=2.16; 2.01–2.32). Mean survival for the methylated group was 24.22 months, whereas mean survival for the unmethylated group was 17.55 months. CONCLUSION: These results confirm that MGMT promoter methylation is the single most important factor affecting survival among GBM patients and MGMT promoter methylation was an independent indicator of better prognosis for GBM patients. The presence of a methylated MGMT promoter is a predictive biomarker for response to alkylator based therapies.